Phenotypic Surveillance of Enterococcus Sp. From A Tertiary Care Regional Hospital: Life Sciences-Microbiology - G Varghese, Jijo; B, Anandharaj; E, Fiji (International Journal of Life Science and Pharma Research, 2022)
Enterococci are ubiquitous pathogens commonly present in gut microbiota in humans/animals that can able to form biofilms which leads to increased antimicrobial resistance. As the treatment of drug resistant Enterococci associated infections is difficult to treat and the mortality rate is rapidly increasing among clinical settings. The present study is aimed to investigate the antimicrobial resistance pattern, virulence genes activation and biofilm forming ability of Enterococcus species isolated from hospital wards in Kerala, India. From January 2018 to March 2019, we collected 100 samples and detected 93 Enterococci isolates which were confirmed by Gram staining and biochemical assay tests. Ability of the isolates to produce biofilms were also studied. In total of 93 enterococci strains, Enterococcus faecalis (85%) was observed as predominant species. Many isolates exhibited multidrug resistance; in particular, 91.30 % isolates of E. faecium and E. faecalis were resistant to five antibiotics. Notably, E. faecalis (88.6%) is more resistant against vancomycin than E. faecium. And, we detected 11virulence genes and 15 antibiotic resistance genes in the tested isolates. E. faecium had exhibit higher level of biofilm formation than E. faecalis. This is the first report to exhibit hospital wards (ICU wards) as reservoir for multidrug resistant enterococci with potential of virulence and biofilm formation. It may ease to transmit the organism from environments into humans. This study provides some useful data about enterococci and suggesting that a regular maintenance of aseptic condition and patients surveillance is needed to control the pathogenesis of Enterococci from hospitals.